On the origin of the mesospheric quasi-stationary planetary waves in the unusual Arctic winter 2015/2016 - V. Matthias; V. Matthias; M. Ern (Atmospheric Chemistry and Physics, 2018)
The midwinter 2015/2016 was characterized by an unusually strong polar night jet (PNJ) and extraordinarily large stationary planetary wave (SPW) amplitudes in the subtropical mesosphere. The aim of this study is, therefore, to find the origin of these mesospheric SPWs in the midwinter 2015/2016 study period. The study duration is split into two periods: the first period runs from late December 2015 until early January 2016 (Period I), and the second period from early January until mid-January 2016 (Period II). While the SPW 1 dominates in the subtropical mesosphere in Period I, it is the SPW 2 that dominates in Period II. There are three possibilities explaining how SPWs can occur in the mesosphere: (1) they propagate upward from the stratosphere, (2) they are generated in situ by longitudinally variable gravity wave (GW) drag, or (3) they are generated in situ by barotropic and/or baroclinic instabilities. Using global satellite observations from the Microwave Limb Sounder (MLS) and the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) the origin of the mesospheric SPWs is investigated for both time periods. We find that due to the strong PNJ the SPWs were not able to propagate upward into the mesosphere northward of 50° N but were deflected upward and equatorward into the subtropical mesosphere. We show that the SPWs observed in the subtropical mesosphere are the same SPWs as in the mid-latitudinal stratosphere. Simultaneously, we find evidence that the mesospheric SPWs in polar latitudes were generated in situ by longitudinally variable GW drag and that there is a mixture of in situ generation by longitudinally variable GW drag and by instabilities at mid-latitudes. Our results, based on observations, show that the abovementioned three mechanisms can act at the same time which confirms earlier model studies. Additionally, the possible contribution from, or impact of, unusually strong SPWs in the subtropical mesosphere to the disruption of the quasi-biennial oscillation (QBO) in the same winter is discussed.